An improved method for point deflection measurements on rectangular membranes. (5th November 2016) - Merle, Benoit; Nicholson, Kyle S.; Herbert, Erik G.; Göken, Mathias
Abstract: In this work, the recent theoretical advances for evaluating point deflection experiments are reviewed and further refined. An improved experimental approach based on measuring the contact stiffness during nanoindentation is implemented and applied to the evaluation of the residual stress in SiNx and gold membranes. The accuracy of the point deflection experiments is assessed by evaluating the same set of samples with the bulge test reference technique and comparing the residual stress results. It is shown that the new experimental method greatly improves the reproducibility of the measurement and that the updated evaluation scheme leads to a more reliable residual stress value. Graphical abstract: Highlights: Residual stresses are measured from small deflection experiments on long rectangular membranes Continuous measurement of stiffness during nanoindentation improves reliability and repeatability of the experimental data The evaluation procedure is improved by adjusting the geometry factors to the elastic properties of the sample